2011
DOI: 10.1002/met.241
|View full text |Cite
|
Sign up to set email alerts
|

Study of Stratosphere‐troposphere exchange events of ozone in India and Greece using ozonesonde ascents

Abstract: Stratosphere-troposphere Exchange (STE) is an important factor controlling the budget of ozone in the upper troposphere and lower stratosphere. Studies of STE events in India are so far restricted to co-ordinated campaigns, and measurements over longer periods are relatively scarce. In the light of this observation, this paper aims to identify the Indian latitudes most likely to be affected by STE, the frequency of occurrence of shallow and deep STE events, the depth up to which the ozone from the stratosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Further studies have shown that ozone depletion occurred not only in the Antarctic but also in other latitudes, which indicates it has become a global phenomenon [6][7][8][9]. Apart from the anthropogenic factor, there are many geophysical parameters that affect the ozone, including the Quasi-Biennial Oscillation, an 11-year cycle of the solar flux, the scaling effect in planetary science, the stratosphere-troposphere exchange, and so on [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have shown that ozone depletion occurred not only in the Antarctic but also in other latitudes, which indicates it has become a global phenomenon [6][7][8][9]. Apart from the anthropogenic factor, there are many geophysical parameters that affect the ozone, including the Quasi-Biennial Oscillation, an 11-year cycle of the solar flux, the scaling effect in planetary science, the stratosphere-troposphere exchange, and so on [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The smog/haze-fog formation basically depends on the atmospheric aerosol loading levels and meteorological state, particularly, on air humidity. Important factors defining or influencing the loadings of the atmospheric air with polluting aerosols or chemical compounds and, by this manner, the occurrence and evolution of smog/haze-fog, are the natural air circulations and solar irradiation [24,91,92], as well as some anthropogenic ones resulting from traffic or industrial fuel combustion, heating, fires, or of other industrial and construction human activities [93][94][95].…”
Section: Impacts On Air Qualitymentioning
confidence: 99%
“…The simulation at time t can be calculated by the previous at time t − 1 and the evolution rules of Formulas (4)- (6). Assuming that the simulation states of the fuzzy cognitive map at time t are A (t) = A 1 (t), .…”
Section: Outputs: the Relationship Degrees In The Fuzzy Cognitive Mapmentioning
confidence: 99%
“…In addition, there are also other possible factors that may affect haze-fog like atmospheric circulation, solar radiation, traffic, industrial emissions, fires, etc. [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%